Camp damascus eaudiobook - Tingle, Chuck (Macmillan Audio, 2023)
"Wilson narrates with emotional depth, conveying all of Rose's intelligence, inquisitiveness, and fear as she's hunted by otherworldly beings." - AudioFile "A joyful, furious romp through dark places, Tingle proves he's as good at fear as he is at love." ―T. Kingfisher, bestselling author of What Moves the Dead From beloved internet icon Chuck Tingle, Camp Damascus is a searing and earnest horror debut about the demons the queer community face in America, the price of keeping secrets, and finding the courage to burn it all down. Welcome to Neverton, Montana: home to a God-fearing community with a heart of gold. Nestled high up in the mountains is Camp Damascus, the self-proclaimed "most effective" gay conversion camp in the country. Here, a life free from sin awaits. But the secret behind that success is anything but holy. And they'll scare you straight to hell. A Macmillan Audio production from Tor Nightfire.